1982
DOI: 10.1111/j.1745-6584.1982.tb02764.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Aldicarb in Ground Water in Selected Areas of the Central Sand Plain of Wisconsin

Abstract: The goal of this study was to provide a preliminary assessment of the occurrence and movement of the pesticide aldicarb in ground water in the Central Sand Plain of Wisconsin. Aldicarb concentrations in ground water beneath three main study fields and two subsidiary fields were monitored during the period December 1980–August 1981. A total of 67 well points, some nested, and one multilevel sampler were installed for this study. In addition, 25 private wells and seven irrigation wells were sampled. The data col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Tests conducted in 1980 and 1981 by the University of Wisconsin, Wisconsin State agencies and Union Carbide Agricultural Products Co. showed that traces of aldicarb residues may appear in potable well water from shallow wells located near agricultural land [ 1,2]. The appearance of aldicarb residues in drinking water in the Central Sands area of Wisconsin was brought about by a combination of factors, including extensive aldicarb usage, highly permeable and acidic soils, high water recharge rate, low soil organic matter content, low soil and water temperatures, low soil microbial activity and shallow drinking water wells.…”
Section: Introductionmentioning
confidence: 99%
“…Tests conducted in 1980 and 1981 by the University of Wisconsin, Wisconsin State agencies and Union Carbide Agricultural Products Co. showed that traces of aldicarb residues may appear in potable well water from shallow wells located near agricultural land [ 1,2]. The appearance of aldicarb residues in drinking water in the Central Sands area of Wisconsin was brought about by a combination of factors, including extensive aldicarb usage, highly permeable and acidic soils, high water recharge rate, low soil organic matter content, low soil and water temperatures, low soil microbial activity and shallow drinking water wells.…”
Section: Introductionmentioning
confidence: 99%
“…Aldicarb tends to concentrate near the water table and does not mix thoroughly in the aquifer profile (Rothschild, Manser, and Anderson, 1982); hence, the only mixing effect to be considered here is that due to pumping at the well site. Thus, the two-dimensional transport model is used without modifications except for adjusting the depth parameter to reflect the well's depth rather than the aquifer depth.…”
Section: Prev Firstmentioning
confidence: 99%
“…Once these chemicals enter the soil environment, they undergo physical and chemical changes, including combination with other chemicals and may enter the food chain and accumulate in living organisms. It has been reported by several researchers1–8 that pesticides are found in soil, surface and ground‐water samples as pollutants. This has contributed to the need for experimental studies of pesticide adsorption by soils, because adsorption is the most significant phenomenon influencing their fate and effectiveness in the soil environment.…”
Section: Introductionmentioning
confidence: 99%